Immunological parameters of Javanese carp Puntius gonionotus (Bleeker) exposed to copper and challenged with Aeromonas hydrophila - Shariff, M.; Jayawardena, P.A.H.L.; Yusoff, F.M.; Subasinghe, R. (Academic Press, 2001)
This study was to determine the median lethal concentration (LC50) of copper to Javenese carp, Puntius gonionotus (Bleeker), and the immune response after the fish were exposed to sublethal levels of copper and challenged with formalin killed Aeromonas hydrophila. The LC50of copper on P. gonionotus at 24, 48, 72, 96 and 120h were estimated as 2·17, 0·91, 0·57, 0·53 and 0·42mg l-1, respectively. To determine the effect of copper on the immune system, fish were exposed for 66 days to 0·05, 0·10 and 0·15mg Cu l-1. After 56 days of initial exposure to copper, fish were challenged with 0·1ml of 4·5×105cfu ml-1formalin killed A. hydrophila and maintained in the same concentration of copper. After the challenge, the immune response was monitored for 2 weeks using haematological and serological assays. During the initial phase of exposure to copper, significant changes were noted in the white blood cell, lysozyme, potential killing activity, total plasma protein, total immunoglobulin and haematocrit levels between the control and treated fish. One week after challenge with A. hydrophila, there was a significant increase in the values of white blood cells, total protein and total immunoglobulin compared to the values before the challenge. However, these values were not significantly different (P> 0·05) between the control and the treated fish. In contrast, NBT and lysozyme assays exhibited a significant difference (P< 0·05) in fish exposed to 0·10mg Cu l-1(0·525±0·17; 24·42±3·35×102μmg ml-1) and 0·15mg Cu l-1(0·536±0·19; 21·78±1·29×102μmg ml-1) compared to the control (0·746±0·31; 30·73±5·42×102μmg ml-1) after the bacterial challenge (day 61). There was however no significant difference (P> 0·05) in NBT and lysozyme levels in fish exposed to lower level of copper (0·05mg Cu l-1), suggesting the absence of immunosuppressive effects at lower level of exposure.